Erratum: Cytosolic Hsp70 as a biomarker to predict clinical outcome in patients with glioblastoma (PLoS ONE (2019) 14:8 (e0221502) DOI: 10.1371/journal.pone.0221502) - Lämmer, Friederike; Delbridge, Claire; Würstle, Silvia; Neff, Frauke; Meyer, Bernhard; Schlegel, Jürgen; Kessel, Kerstin A.; Schmid, Thomas E.; Schilling, Daniela; Combs, Stephanie E. (PLoS ONE, 2021)
The raw data underlying Figs 3 and 4 are missing from the list of Supporting Information. The authors have provided the data as Supporting Information file S1 Dataset. With this correction [1], all relevant data are now provided. The Data Availability statement for this paper is incorrect. The correct statement is: All relevant data are within the paper and its Supporting Information files.
CRIS-Team Scopus Importer:2023-03-08